Fast MRI whole brain segmentation with fully convolutional neural networks - Roy, Abhijit Guha; Conjeti, Sailesh; Navab, Nassir; Wachinger, Christian (Informatik aktuell, 2018)
Whole brain segmentation from structural MRI-T1 scan is a prerequisite for most morphological analyses, but requires hours of processing time and therefore delays the availability of image markers after scan acquisition. We introduced a fully convolution neural network (F-CNN) that segments a brain scan in several seconds [1]. Training deep F-CNNs for semantic image segmentation requires access to abundant labeled data.
CRIS-Team Scopus Importer:2023-03-08